2022
DOI: 10.1146/annurev-arplant-102820-091838
|View full text |Cite
|
Sign up to set email alerts
|

Embryo–Endosperm Interactions

Abstract: In angiosperms, double fertilization triggers the concomitant development of two closely juxtaposed tissues, the embryo and the endosperm. Successful seed development and germination require constant interactions between these tissues, which occur across their common interface. The embryo–endosperm interface is a complex and poorly understood compound apoplast comprising components derived from both tissues, across which nutrients transit to fuel embryo development. Interface properties, which affect molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 182 publications
(208 reference statements)
0
41
0
1
Order By: Relevance
“…In summary, our data suggest that the seeds of SmBRX transgenics are substantially bigger than in wildtype. Dried A. thaliana seeds largely represent the mature embryo, because the endosperm is essentially consumed as embryogenesis progresses (Doll and Ingram, 2022; Lafon-Placette and Kohler, 2014). This suggested that mature SmBRX transgenic embryos are bigger than wildtype embryos, which turned out to be the case (Figure S4C and D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, our data suggest that the seeds of SmBRX transgenics are substantially bigger than in wildtype. Dried A. thaliana seeds largely represent the mature embryo, because the endosperm is essentially consumed as embryogenesis progresses (Doll and Ingram, 2022; Lafon-Placette and Kohler, 2014). This suggested that mature SmBRX transgenic embryos are bigger than wildtype embryos, which turned out to be the case (Figure S4C and D).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, SmBRX/AtBRX sml -conferred gain-of-function might reflect reduced abscisic acid sensitivity, because loss-of-function mutants in the downstream abscisic acid effector ABSCISIC ACID-INSENSITIVE 5 form bigger seeds (Cheng et al, 2014; Li and Li, 2016), and because the abscisic acid antagonist, gibberellic acid, promotes post-germination root meristem growth (Achard et al, 2009; Moubayidin et al, 2010). These leads could be investigated in follow up experiments, which might also clarify why exactly SmBRX/AtBRX sml seeds are bigger, since multiple interactions between seed coat, endosperm and embryo contribute to the final outcome of seed development (Doll and Ingram, 2022; Lafon-Placette and Kohler, 2014; Li and Li, 2016). Given the high conservation of BRX family proteins in both non-vascular and non-seed plants, such analyses might also aid in the characterization of their ancestral function.…”
Section: Discussionmentioning
confidence: 99%
“…A hypothesis that is often mentioned in papers and reviews is the potential movement of sRNA from the fertilized endosperm to the embryo to direct the increase in DNA methylation observed during embryo development. Such movement, if occurring, would have to happen at early stages of embryo development before the embryo becomes clearly symplastically and apoplastically isolated from the endosperm 9 . To test whether we could observe a silencing movement from the endosperm to the embryo, we quantified the mean fluorescence intensity in the different cell types of the developing seed (endosperm, embryo, suspensor and integuments) at different time-points of early seed development in the pDD65hp;LIG1GFP lines (Fig1E-G, J and FigS2).…”
Section: Main Textmentioning
confidence: 99%
“…On the one hand, important advances on the molecular regulation of key actors have been achieved, as exemplified for DELAY OF GERMINATION-1 (DOG1), the most popular regulator of dormancy [1]. On the other hand, new directions have been explored, from which epigenetic regulation and endosperm-embryo crosstalk emerged as hot topics for future research [2,3]. Finally, the abundance of omics data paves the way to system biology-based approaches and the construction of integrative models.…”
mentioning
confidence: 99%
“…The specific functions of the different seed tissues, as well as their functional interactions, have been paid increasing attention and bridge seed development and seed germination processes over space and time [3]. These issues are addressed in a review article by Miray et al [8] and in a research article by Sun et al [9].…”
mentioning
confidence: 99%